(untitled) (Journal of Applied Business and Economics, 2023)
The national government encourages Dutch households and businesses to use less natural gas and more sustainable heat. The Sustainable Energy Investment Subsidy (Dutch: Investeringssubsidie Duurzame Energie or ISDE), which has been in place since 2016, provides a subsidy for the purchase of solar boilers, heat pumps, biomass boilers and pellet stoves. The scheme is meant for both private individuals and business users. An important element in the evaluation of the ISDE was the ‘additionality’ of the scheme. This was evaluated by the Dutch organization for applied natural scientific research (TNO) in 2018 and by SEO Economic Research (SEO) in 2019. In this paper the evaluation methods are described, compared and critically reviewed in order to identify uncertainties and limitations of the methods and possible improvements. The methods lead to different results for the additionality of the ISDE scheme per type of device and this paper looks into the reasons for this. Additional evaluation studies’ results depend on many factors elaborated on in this paper.